2018
DOI: 10.1177/1940082918799476
|View full text |Cite
|
Sign up to set email alerts
|

An Insight Into the Diet and Prey Preference of Tigers in Bardia National Park, Nepal

Abstract: We studied the diet and prey preferences of tigers (Panthera tigris tigris Linnaeus, 1758) in Bardia National Park, Nepal using DNA-based techniques from their scat samples. Remains of prey species in scats were identified through microscopic hair morphology analysis. Of 101 scats, DNA was extracted from 84 samples and 75 were assigned to tigers (34 males and 41 females). We found seven and six prey species in the diet of male tiger and female tiger, respectively. The diet of male and female tigers did not dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 51 publications
(82 reference statements)
0
27
0
Order By: Relevance
“…Tiger tracks (> 8 cm pad width) and scrapes (> 35 cm long and > 19 cm wide) are larger than leopard tracks (< 6.5 cm pad width) and scrape (< 25 cm long and < 15 cm wide). In a similar study in Bardia NP, using molecular identification of the carnivore, Upadhyaya et al (2018) reported high accuracy of field identification of scats (n = 101). Prey remains in the scat such as hairs, feathers, bones, hooves and teeth were separated.…”
Section: Diet Of Tigers and Leopardsmentioning
confidence: 87%
“…Tiger tracks (> 8 cm pad width) and scrapes (> 35 cm long and > 19 cm wide) are larger than leopard tracks (< 6.5 cm pad width) and scrape (< 25 cm long and < 15 cm wide). In a similar study in Bardia NP, using molecular identification of the carnivore, Upadhyaya et al (2018) reported high accuracy of field identification of scats (n = 101). Prey remains in the scat such as hairs, feathers, bones, hooves and teeth were separated.…”
Section: Diet Of Tigers and Leopardsmentioning
confidence: 87%
“…Here, we classified the assemblage of these cervids as a mesofaunal deer community (Ahrestani & Sankaran, 2016). Chital is the most abundant and at the moment the primary prey species of the tiger in Bardia NP (Upadhyaya et al, 2018) with a reported density of ~50 deer.km −2 (DNPWC & DFRS, 2018). Muntjac and sambar are forest dwellers; are classified as browsers (Ahrestani & Sankaran, 2016) and are seen very rarely in the grasslands.…”
Section: Methodsmentioning
confidence: 99%
“…We found that leopards caused the majority of livestock loss around Bardia National Park, in contrast to Acharya et al (2016) who reported that leopards contributed to 21% of livestock depredation in Nepal. Signs of leopards were found primarily near the edge of the Park in Bardia (Studsrød & Wegge, 1995; Tamang & Baral, 2008; Upadhyaya et al, 2018), which has also been reported in Nepal's Chitwan National Park (Bhattarai & Kindlmann, 2012) and Macharia National Park, Pakistan (Dar et al, 2009). Livestock loss was related to the number of livestock held in the area, which is similar to findings of Tamang & Baral (2008) from Bardia, Oli et al (1994) from the Annapurna conservation area in Nepal, and Wang & Macdonald (2006) from Bhutan.…”
Section: Discussionmentioning
confidence: 79%